Entrepreneur´s profile and factors that influence the potential of business internationalization - Vargas Hernández, José (2020)
Trading outside the political borders of Mexico is essential in terms of macroeconomic stability in this country, through the export channel, which is currently highly integrated into the economic activity of our northern neighboring country. 79.95% of Mexican exports in 2017 went to the United States of America with a worth of US $ 327,358 million. This paper attempts to describe the contextual framework of international entrepreneurship and the importance of the entrepreneur's profile in relation to success in doing business abroad.